Impact of Sustained Cardiac Tachyarrhythmias Recorded in Coronary Intensive Care Unit on Short- and Long-Term Mortality and Duration of Hospitalization. (July 2021) - Papakonstantinou, Panteleimon E.; Malliou, Angelliki; Chlouverakis, Gregory; Kallergis, Eleftherios; Mavrakis, Hercules; Parthenakis, Frangiskos; Vardas, Panos E.; Simantirakis, Emmanuel N.
Background: Studies conducted in coronary intensive care units (CICUs) have demonstrated that tachyarrhythmias are associated with increased mortality after acute coronary syndromes (ACSs). However, the data for tachyarrhythmias occurred in CICUs due to a variety of cardiovascular disorders are limited. Methods: We conducted a single-center prospective observational study, which included consecutive CICU patients (January 1, 2014 to May 31, 2018). We recorded the ventricular arrhythmias (VAs), supraventricular tachycardias (SVTs), and days of CICU hospitalization. The patients were followed up for 6 months after CICU discharge. Results: A total of 943 patients (age: 66.37 ±15.4 years; 673 males [71.4%]) were included. Patients with tachyarrhythmias had higher in-CICU mortality (8.0% vs 4.1%, P = .029, odds ratio [OR]: 2.04, 95% confidence interval [CI]: 1.08-3.86) and higher 6-month all-cause mortality (12.8% vs 6.1%, P = .002, OR: 2.27, 95% CI: 1.35-3.83) than those who did not develop tachyarrhythmias. Ventricular arrhythmias was significantly associated with higher all-cause mortality than no tachyarrhythmia (15.4% vs 6.1%; P = .001) or SVTs (15.4% vs 7.0%; P = .001). The mean duration of hospitalization for the patients with tachyarrhythmias was 3.89 ± 4.90 days, while for the patients without was 2.79 ± 3.31 days ( P < .001). Patients without ACS had higher short- and long-term mortality compared to patients with ACS (9.2% vs 2.9%, P < .001 and 12.9% vs 4.9%, P < .001). Conclusions: Tachyarrhythmias were associated with prolonged CICU hospitalization, while non-ACS cardiovascular disorders and the occurrence of VAs were associated with increased short- and long-term mortality.